Morocco Teachers : SABER Country Report 2016 - Cross, Jess (World Bank, Washington, DC, 2017)
Evidence on the impacts of many teacher policies remains insufficient and scattered, and the impact of many reforms depends on specific design features. In addition, teacher policies can have very different impacts, depending on the context and other education policies in place. Systems approach for better education results (SABER) - teachers, aims to help fill this gap by collecting, analyzing, synthesizing, and disseminating comprehensive information on teacher policies in primary- and secondary-education systems around the world. SABER - teachers collects data on 10 core teacher policy areas to offer a comprehensive, descriptive overview of the teacher policies that are in place in each participating education system. To offer informed policy guidance, SABER - teachers analyzes the information collected to assess the extent to which the teacher policies of an education system are aligned with policies shown by research evidence to have a positive effect on student achievement. This report presents results of the application of SABER - teachers in Morocco. It describes Morocco’s performance for each of the eight teacher policy goals, alongside comparative information from education systems that have consistently scored high results in international student achievement tests and have participated in SABER - teachers.